Peritoneal Dialysis Catheter Implantation: Avoiding Problems and Optimizing Outcomes. Issue 1 (23rd October 2014) - Crabtree, John H.
Abstract The success of peritoneal dialysis (PD) as renal replacement therapy is dependent upon the patient having a functional long‐term peritoneal access. There are a number of identified best practices that must be adhered to during PD catheter placement to achieve a durable and infection‐resistant access. The clinical setting, available resources, and the employed catheter insertion method may not always permit complete adherence to these practices; however, an attempt should be made to comply with them as closely as possible. Although omission of any one of the practices can lead to catheter loss, departures from some are committed more frequently, manifesting as commonly occurring clinical problems, such as drain pain, catheter tip migration, omental entrapment, pericatheter leaks and hernias, and poor exit‐site location. Understanding the technical pitfalls in PD catheter placement that lead to these problems, enable the provider to modify practice habits to avoid them and optimize outcomes.